2006
DOI: 10.1007/bf02702869
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of transparent exopolymeric particles (TEP) and particle-associated carbohydrates in the Dona Paula bay, west coast of India

Abstract: Surface seawater samples were collected over a period of 27 months at a shallow water station in Dona Paula bay from 1998-2000. The samples were analyzed to assess the seasonal variations, inter-annual variability and the contributions of i) transparent exopolymeric particles (TEP) concentration, ii) two forms of particle-associated carbohydrates-1.5M NaCl/saline extracted and greater than bacterial-C (4.6% ± 4.6%) or carbohydrate-C (< 3.8 %). Despite its greater contribution to the organic carbon pool, the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
12
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 46 publications
9
12
1
Order By: Relevance
“…The TEP levels we measured at the SWAS are generally within the range of those reported for coastal areas Riebesell et al, 1995;Kiorboe et al, 1996;Hong et al, 1997;Jähmlich et al, 1998;Wild, 2000;Ramaiah et al, 2001;Engel et al, 2002b;García et al, 2002;Radic et al, 2005;Scoullos et al, 2006;Sugimoto et al, 2007;Harlay et al, 2009Harlay et al, , 2010Wurl et al, 2009;Fukao et al, 2011;Klein et al, 2011;Sun et al, 2012;Van Oostende et al, 2012;Dreshchinskii and Engel, 2017;Jennings et al, 2017). Only two studies, in the western Baltic Sea and the Dona Paula Bay (Arabian Sea), reported TEP levels higher than ours (Engel, 2000;Bhaskar and Bhosle, 2006).…”
Section: Teps Across the Surface Atlantic Oceansupporting
confidence: 83%
See 2 more Smart Citations
“…The TEP levels we measured at the SWAS are generally within the range of those reported for coastal areas Riebesell et al, 1995;Kiorboe et al, 1996;Hong et al, 1997;Jähmlich et al, 1998;Wild, 2000;Ramaiah et al, 2001;Engel et al, 2002b;García et al, 2002;Radic et al, 2005;Scoullos et al, 2006;Sugimoto et al, 2007;Harlay et al, 2009Harlay et al, , 2010Wurl et al, 2009;Fukao et al, 2011;Klein et al, 2011;Sun et al, 2012;Van Oostende et al, 2012;Dreshchinskii and Engel, 2017;Jennings et al, 2017). Only two studies, in the western Baltic Sea and the Dona Paula Bay (Arabian Sea), reported TEP levels higher than ours (Engel, 2000;Bhaskar and Bhosle, 2006).…”
Section: Teps Across the Surface Atlantic Oceansupporting
confidence: 83%
“…A previous study in a eutrophic system reported TEP-C as the dominant POC contributor (Yamada et al, 2015), whereas others found that phyto-C represented the largest share to POC compared to TEP-C and HP-C (Bhaskar and Bhosle, 2006;Ortega-Retuerta et al, 2009b;de Vicente et al, 2010). With our results taken all together, we hypothesize that in oligotrophic conditions TEP-C is the predominant POC fraction, because nutrient limitation favors TEP production by phytoplankton and limits TEP consumption by bacteria.…”
Section: Teps As An Important Contributor To Ocean Surface Pocmentioning
confidence: 97%
See 1 more Smart Citation
“…For these reasons, the direct transposition of such a relationship to estimates of CaCO 3 dissolution rates in the field was not possible from our data-set. The contribution of TEP-C to the POC in the top 40 m averaged 26 ± 4% (n = 31), which is higher than previous estimates in the same area (12%; Harlay et al, 2009), along a transect in the northeast North Atlantic (17 ± 7%; Engel, 2004), and in the Bay of Bengal (7%; Bhaskar and Bhosle, 2006).…”
contrasting
confidence: 42%
“…The TEP levels we measured at the SWAS are generally within the range of those reported for coastal areas (Passow and Alldredge, 1995;Riebesell et al, 1995;Kiorboe et al, 1996;Hong et al, 1997;Jähmlich et al, 1998;Wild, 2000;Ramaiah et al, 2001;Engel et al, 2002b;García et al, 2002;Radic et al, 2005;Scoullos et al, 2006;Sugimoto et al, 2007;Harlay et al, 2009;Wurl et al, 2009;Harlay et al, 2010;Fukao et al, 2011;Klein et al, 2011;Sun et al, 2012;Van Oostende et al, 2012;Dreshchinskii and Engel, 2017;Jennings et al, 2017). Only two studies, in the western Baltic Sea and the Dona Paula Bay (Arabian Sea), reported TEP levels higher than ours (Engel, 2000;Bhaskar and Bhosle, 2006).…”
Section: )supporting
confidence: 83%